THE SIAMESE GOVERNMENT’S RESPONSES TO WESTERN FORCES AT THE TIME OF KING MONGKUT (1851-1868) - Nguyen Tien Dung (In Gremium. Studies in History, Culture and Politics, 2017)
Since the second half of the nineteenth century, when the Europeans with their gunboats appeared in almost evrey corners of Asian waters, the sovereignty of many countries in the region was put under the serious threats. Yet, Siam is the only country in Southeast Asia which successfully safeguarded its national independence and sovereignty. Most scholars have explained the success of Siam in terms of its unique positions as “a buffer zone” between two competing colonial powers, namely the French and the British. This article examines the King Mongkut’s consciousness of national sovereignty and interests and his wise response to Western Forces. It argues that instead of the geographical position, decisions made by the King Mongkut in response to foreign challenges were the main reason behind the success of Siam.